Critical Success Factors of IT/IS Outsourcing in Malaysian Public Sectors - Ghazali, Noura Binti Mohamad; Bin Hasan, Zainuddin (International Journal of Engineering and Technology, 2018)
IT/IS outsourcing has been in the IT industry for so many years. Many studies have been carried out about the success factors in IT/IS Outsourcing. However, most authors focused more on the success factors in the private sector compared to the public sector. This paper focuses on understanding the benefits and determining the critical success factors of information technology/information system (IT/IS) outsourcing in the public sector. Apart from that, the reader is also being exposed to the reasons why an organization opt for outsourcing. This paper reviews published journals and reports from various authors, focusing on the connections and similarities. It then extracts and summarize the benefits and critical success factors that organization can refer to before organization endeavors in IT/IS outsourcing activities.